Post-thrombotic syndrome. Issue 3 (1st March 2002) - Barnes, C; Newall, F; Monagle, P
Abstract : Post-thrombotic syndrome (PTS) is a potentially disabling complication occurring in up to 67% of adult patients following deep venous thrombosis (DVT). PTS has recently been recognised in children. We present three cases of symptomatic PTS in children, which occurred following the use of central venous lines (CVLs). In two cases, no symptoms of acute thrombosis were noted. The cases highlight the clinical presentation of this syndrome. A review of the literature revealed two reports describing PTS occurring in children following DVT with an estimated incidence of 7–12%. It is concluded that PTS is an important complication of DVT in children. The clinical findings of pain, swelling, and brawny induration are similar to adult patients. The effect on growing limbs is not known. Paediatricians should be aware of the potential of PTS in all children who are at risk of DVT, including patients with malignancy, congenital heart disease, and children who have had previous CVLs, even in the absence of documented acute DVT.